The Flexophone : A study on controlling sound with EMG signals - Puhtila, Panu (My University, 2024)
In this thesis, the author will conduct a user experience research on the possibilities of using electromyographic (EMG) signals to control the sound produced by software oscillator. A simple software oscillator and a rudimentary interface using the EMG signals was implemented for the means of conducting the research, and 5 people with previous musical background were recruited to test the interface. The test subjects were given a questionnaire charting their experience, which was analyzed to answer the question of whether this kind of interface is viable for controlling of sound to be used in music. Results from this study indicate that there could be interest towards this kind of interface among people who practice music, as the average of overall experience was rated 3.72 in Likert scale between 1 and 5. 4 out of 5 test users also reported interest in to using this kind of interface in actual musical performance. However, results also highlight the technical issues this kind of interface must address for it to be viable for and interesting to musicians. Among the issues identified in this research are problems with keeping the rhythm, having wide enough scale of possible sounds and the discomfort caused by the removal of electrodes from the skin. These negative aspects are a matter of technical implementation and will be solved in future research.
Keywords: EMG, interface design, music, sound control, interaction design, HCI